Changements climatiques, migrations et défis de la gestion de l’environnement : le cas d’un village au cœur de la tourmente au Burkina Faso - Ibrahim Ouattara (Éditions en environnement VertigO, 2009)
Global changes have detrimental consequences on the conditions of life in Sahelian countries. The experience of the village of Koumbili (Burkina Faso), documented through a participatory rural appraisal (PAR) conducted in 2005, brings a concrete understanding of how actual climatic and political changes can bring about human behaviours that jeopardize the integrity of fragile ecosystem. The case of Koumbili also allows an outlook on various mechanisms which aim at strengthening local sustainable management and local organization capacities in the region considered. PAR revealed that the exploitation of the village’s natural resources has intensified markedly, due to the rising of the population. A large part of the latter resulted from migrations related to the drying out of neighbouring regions and from displacements related to the Ivory Coast’s crisis. Conservation of land production potential and access to water, have thus become the cause of tensions and conflicts in the village populations. This issue can be addressed by enhancing village associations with educational institutions. Universities have an important role to play in this process, and more precisely in sustainable development and in community-based social innovation. This is the rational behind the institutional reinforcement partnership between Université de Moncton and Université de Ouagadougou. The present case study derives from this partnership. Its aim is to reinforce the pertinence and the impact of university teaching and research on local communities. It is based on interdisciplinarity and wishes to bring the university “closer” to rural communities in order to develop mutual learning and long-lasting interactions, in order to build the capacities of organisation and action at the local level.